Gender Differences in Students’ Achievement in Literary Appreciation Using Reciprocal Peer Tutoring Strategy - Assimonye, Augusta Chiedu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Students’ low performance in literary appreciation remains a persistent challenge in secondary schools, often linked to conventional, teacher-centered instructional methods that restrict learners’ interaction and critical engagement with texts. Gender disparities in academic achievement have further raised concerns about the influence of teaching strategies on male and female learners. This study therefore examined gender differences in students’ achievement in literary appreciation using the Reciprocal Peer Tutoring (RPT) strategy. The study used a quasi-experimental pretest-posttest non-equivalent control group design to compare the effects of reciprocal peer tutoring and conventional teaching on Literature in English students in Anambra State. A sample of 65 Senior Secondary II students participated. Data were collected using a validated and reliable Literature Achievement and Retention Test. Teachers implemented the six-week treatment, and tests measured achievement and retention. Data were analyzed using mean, standard deviation, and ANCOVA at a 0.05 significance level to determine instructional effectiveness. The result showed that male and female students taught literary appreciation using the reciprocal peer tutoring strategy recorded improvement in performance. Male students (11) had a pretest mean score of (52.32) and a posttest mean of (65.12) with a mean gain of (12.80), while female students (20) had a pretest mean of (54.40) and posttest mean of (64.32) with a mean gain of (9.92). Although males achieved slightly higher, the ANCOVA result with a P-value of (0.157) indicated no significant difference between male and female students’ achievement scores. The study concluded that RPT promotes active learning, cooperation, and improved achievement in literary appreciation irrespective of gender. It recommended the integration of RPT into literature teaching to promote equal learning opportunities and improved academic outcomes.